Because of Mr. Terupt - Buyea, Rob. (New York : Yearling, 2011)
Seven fifth-graders at Snow Hill School in Connecticut relate how their lives are changed for the better by "rookie teacher" Mr. Terupt.
"A Yearling book."
School Library Journal starred
Wilson's Children
Wilson's Junior High School
Booklist, October 2010
Horn Book, May 2011
Keywords: Families -- Connecticut -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Schools -- Juvenile fiction; Teacher-student relationships -- Juvenile fiction; Teachers -- Juvenile fiction; Family life -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction; Teacher-student relationships -- Fiction; Teachers -- Fiction; Family life -- Connecticut -- Fiction; Interpersonal relations -- Fiction; School stories; Teacher-student relationship -- Fiction; Teachers -- Fiction; Connecticut -- Juvenile fiction; Connecticut -- Fiction; Connecticut -- Fiction